PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN QUIZALIZE TERHADAP PEMAHAMAN SISWA PADA MATA PELAJARAN TIK DI SMP NEGERI 1 BONTONOMPO - Heri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study investigates the effect of using Quizalize digital media on the understanding of 8th-grade students in TIK (Information and Communication Technology) subjects at SMP Negeri 1 Bontonompo. The research problem was identified from the low level of student engagement and understanding, which was linked to conventional teaching methods. The study's objective was to analyze whether the application of Quizalize media could significantly improve student comprehension. Employing a quantitative experimental approach with a one-group pretest-posttest design, the study involved 30 students from class VIII A. Data was collected through observation sheets for student activity and pretest-posttest scores. The findings demonstrate a significant positive influence on student understanding. The average score increased from 56.28 in the pretest to 91.71 in the posttest. This improvement was supported by observation data showing increased student activity, rising from 80.40% in the first session to 84.48% in the third. The analysis confirms that using Quizalize media creates a more active and effective learning environment, leading to a substantial enhancement in student comprehension.